FREQUENCY OF HBV INFECTION AND ITS RISK FACTORS IN ASYMPTOMATIC MILITARY PERSONNELS: Frequency of HBV Infection and Its Risk Factors - Kamran, Sultan Mehmood; Iftikhar, Raheel; Wasti, SM Wasim; Awan, Zohaib Iqbal (Pakistan Armed Forces Medical Journal, 2016)
Objective: To determine the frequency of silent Hepatitis B virus (HBV) infection, its symptoms and risk factors in apparently healthy military personnel of Pakistan Army.Study Design: Descriptive cross sectional study.Place and Duration of Study: Department of medicine, Combined Military Hospital Okara from Oct 2012 to Mar 2013.Material and Methods: A total of 6236 healthy troops with age ranging from 18 to 57 years without previous or present history of HBV infection were selected by consecutive sampling from Okara Garrison. Blood samples were subjected to rapid screening of HBV infection using immunochrom atographic (ICT) kits (Intec ® production, Inc) with sensitivity and specificity of 99.8% and 95 % respectively. All positive cases were confirmed by 4th generation ELISA and PCR for HBV DNA were also sent. All infected cases were given a questionnaire about different risk factors of HBV infection. Finally variables were defined qualitatively and quantitatively and frequency, percentage, mean (SD) were calculated. All the data was analyzed using SPSS version 19.Results: Age ranged from 18-57 years with mean age of the study group 27 (±7.2) years. Mean age among those with HBs Ag positive was 32 (±7.3) years. Frequency of HBV infection was 2.03% (127 participants out of 6236) whereas PCR for HBV DNA was positive in 51 out of 127 (40.1%). Most common symptom was anorexia in 16 patients (12.6%) followed by fatigue and fever in 15 patients (11.8%) each. While 42 patients (33.1%) were asymptomatic. Dental procedures was found to be most frequent risk factor (25.9%) followed by previous history of surgery (21.2%).Conclusion: Although pre induction screening of HBV infection is carried out in Pak Army still its prevalence is matched with that of general Pakistani population. Soldiers’ education and immediate vaccination is recommended at time of induction to stop the spread of this dreadful disease in Pak army.